PENGARUH TANGGUNG JAWAB SOSIAL, DIMENSI-DIMENSINYA, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK - Annastasya Wahyuningtyas Pratiwi; Endang Kiswara (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effect of social responsibility, dimensions, and leverage on corporate tax aggressiveness. This research uses social responsibility and its dimensions such as social, governance, economy, and environment, and one of the characteristics of the company is leverage as an independent variable. While the dependent variable of this study is tax aggressiveness. In addition, there are several control variables used in this study such as size, ROA, and capital intensity.The sample of this study are companies listed on the Indonesia Stock Exchange and included in the LQ 45 category in 2014-2017. The sample was chosen using the random sampling method, so the number of samples obtained was 43 companies. The data analysis method used in this study is multiple regression analysis.The results showed that in the first regression model, social responsibility had a significant influence on tax aggressiveness, while leverage had no significant effect on tax aggressiveness. The second regression model shows that social and economic dimensions of social responsibility, as well as leverage have a significant effect on tax aggressiveness.The results of the study show that in the first regression model, social responsibility and leverage have a significant effect on tax aggressiveness. Whereas, in the second regression model shows that the social and economic dimensions of social responsibility, and leverage have a significant effect on tax aggressiveness.